Efficiency, Performance and Robustness of Gas Turbines 2012
DOI: 10.5772/37829
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Micro Gas Turbines

Abstract: Object of the present work is the detailed study, in every its aspect, of Ultra-Micro-Gas- Turbine Generator, that is a power device with high power density. These generators, although the covered power range oscillates between 100 and 500W, is characterized by very reduced overall dimensions: this introduces complications in the design and, above all, the realization of the mechanical components who represents the greater difficulty to exceed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The elements of the tested gas turbine are shown in the Figure 19. Furthermore, the technology of ultra-small gas turbines is presented in [126][127][128][129][130]. Ansaldo Energia [131][132][133] and Capstone [134] are one of the world's leading manufacturers of micro gas turbines.…”
Section: Gas Microturbinesmentioning
confidence: 99%
“…The elements of the tested gas turbine are shown in the Figure 19. Furthermore, the technology of ultra-small gas turbines is presented in [126][127][128][129][130]. Ansaldo Energia [131][132][133] and Capstone [134] are one of the world's leading manufacturers of micro gas turbines.…”
Section: Gas Microturbinesmentioning
confidence: 99%
“…In an electrically coupled turbocharger it is not possible to use the original GT12 component, because its design points depend on the operation of the waste-gate valve, and as such it would not be able to properly respond to the engine conditions nor to supply the required extra power [14][15][16][17][18]. The selection and redesign of the turbine are detailed in a separate work [19], and only a brief summary is repeated here.…”
Section: Preliminary Re-design Of the Turbinementioning
confidence: 99%
“…(3) non-adiabatic flow condition. The effect of low Reynolds-numbers compressor stages has been thoroughly captured in early work [9][10][11] where a correction based on the machine Re-number and surface roughness was proposed. It is suggested that friction losses within the impeller correlate well with the Moody-diagram.…”
Section: Introductionmentioning
confidence: 99%